A LEGAL APPRAISAL OF NIGERIAN COPYRIGHT LAW AND THE AUTHOR - Bielu, John Katchidobelu (NAU Journal of Library and Information Science, 2021)
This study sought to examine the extant copyright regime for protection of the author’s rights and the challenges in Nigeria. Copyright being a lubricant encouraging creativity in the book industry could not also avert some of the problems envisaged in the industry. The inbuilt hiccups in the implementation of the legal framework of books made it difficult for an author to fully earn a living from his works. Textbooks and opinions of authors were x-rayed which revealed the fact that writers face a number of challenges including that today they are compelled to either go into self-publishing or they are forced to subsidize the cost of publishing. It is almost impossible for an author to live on the proceeds of his work. The legal framework and its implementation did not adequately block the economic exploitation of the author’s literary works. There is therefore an urgent need for the law to be amended to block the lacuna in the extant laws. Keywords: Copyright Law, Author’s Right, Licencee, Berne Convention, WIPO, Nigerian Copyright Commission Introduction Copyright Legislation has become the cornerstone for the protection of rights of creators of literary works by providing law enforcement agencies as well as the courts with the instruments to deal with violations of the law. Literary, artistic or musical works are first and foremost owned by a copyright owner. An author is the person chiefly responsible for the intellectual content of a literary or artistic work. The author is the creator or formulator of the ideas to be given to the world through a book, the arranger of the words, pictures, charts, tables and others in which the ideas are to be presented. The author in publishing his literary work may decide to sell that right, lease or assign it to a publisher to reproduce the manuscript in some way and for distribution to the world under contractual agreement. This is known as licencing of copyright. Understandably, the economic proceeds that accrue from the publication and sale of this work belongs to the author. This study tried to examine whether the protection offered by law to the author suffice in all cases and circumstances. This does not however preclude open licencing of online education resources. Legal Framework for Author’s Protection. There are both international and domestic legal regime for protection of the author. These include: International Instruments 1. Article 27(2) of the Universal Declaration of Human Rights 2. International Convention for the Protection of Industrial Property, Paris in 1883 and revised in Lisbon 1958. 3. Berne Convention for the protection of Literacy and Artistic Works, 1886 4. The Rome Convention for the protection of performers, producers of phonograph and Broadcasting Organisation 5. The Patent Cooperation Treaty in 1970 6. Universal Copyright Convention 1971 Municipal Instrument 1. Copyright Act, Cap. C.28 Laws of the Federation of Nigeria, 2004. Copyright Copyright generally is protected under the Universal Declaration of Human Rights (from which many modern municipal copyright statutes derive their inspiration) which provides inter alia that everyone has the right to the protection of the moral and materials interest resulting from which scientific, literacy or artistic production of which he is the author. This is a conscious international policy appreciating the value of creativity and the desirability of those members of the society who through their genius and sweat have preserved, chronicled and perpetuated national development through their literary or intellectual works. The Black’s Law Dictionary define copyright as the right to copy; specifically, a property right in an original work of authorship (including literary, musical, dramatic, cinematographic, pictorial, graphic, sculptural and architectural works, motion pictures and other audio visual works and sound recordings) fixed in any tangible medium of expression, given to the holder the exclusive right to reproduce, adapt, distribute, perform and display the work. This definition is rhetorical and begs the question. However, further explanation ought to be added to the meaning of the subject matter that the province of copyright is communication. It serves to control the copying of protected works by unauthorized persons. Copyright is the exclusive right to do or to control or authorize the doing of certain acts in relation to the work in which the rights subsists. Oguakwa (2005) refers to copyright as the bundle of rights which the legal system recognizes as inhering to the benefits of a creator of a work. Its primary concern is with the expression of ideas rather than the ideas themselves. In Donoghue v Allied Newspapers Ltd, Lord Farewell acknowledging this view said: There is no copyright in an idea or ideas. A person may have a brilliant idea for a story or for a picture or for a play and one which appears to him to be original; but if he communicates that idea to an author or an artist or playwright, the production which is the result of the communication of the ideas to the author or the artist or playwright is the copyright of the person who has clothed the idea in form whether by means of a picture, a play or a book and the owner of the idea has no right in that production. However, for the protection of such expression of ideas, it has to be original, novel and must be fixed in a definite medium of expression now known or later to be developed from which it can be perceived either directly or with the aid of a machine device. Entitlement for Copyright Protection. Under section 1 of the Nigerian Copyright Act, the following are eligible for copyright; a. literary works b. musical works c. artistic works d. cinematograph films e. sound recordings and f. Broadcasts. The Act further provides inter alia; Copyright shall be conferred by this section on every work eligible for copyright of which the author or in the case of a work of joint authorship, any of the authors is at the time when the work is made, a qualified person. The qualification shall be; i. An individual who is a citizen of or is domiciled in Nigeria or; ii. A body corporate incorporated by or under the laws of Nigeria The copyright conferred on the above is in terms of seventy years after the end of the year in which the author dies. In the case of a government or body corporate, seventy years after the end of the year in which the work was first published. In the case of anonymous or pseudonymous literary, musical or artistic works, the copyright shall subsist until the end of the expiration of seventy years from the end of the year in which the work was first published but the term will be calculated in accordance with the first schedule. According to the Act, reference is to be made for the country of origin for eligibility for copyright which was not conferred. Nature of Copyright Generally, the nature of copyright is such that the Act provides that subject to specific exceptions, copyright in a work shall be exclusive right to control the doing in Nigeria of the following acts: a. In a literary or musical works, to do and authorize the doing of any of the following acts: i. Reproduce the work in any material ii. Publish the work iii. Perform the work in public iv. Produce, reproduce, perform or publish any translation of the work. v. Make any cinematograph film or a record in respect of the work. vi. Distribute to the public for commercial purposes, copies of the work by way of rental, lease, hire, loan or similar arrangement. vii. Broadcast or communicate the work to the public by loudspeaker or any other similar device. viii. Make any adaptation of the work. ix. Do in relation to a translation or an adaptation of the work, any of the acts specified. There are also copyright in any artistic work and of cinematography. The doing of any of the acts referred to in subsection (1) of section 6, shall be in respect of the whole or a substantial part of the work either in its original form or in any form recognizably derived from the original. The copyright in the work of architecture shall also include the exclusive right to control the erection of any building which reproduces the whole or a substantial part of the work either in its original form or any form recognizably derived from the original but not the right to control the reconstruction in the same style as the original of a building to which the copyright relates. There is copyright protection under the law for musical works, sound recordings, broadcast and cinematograph film. These are however with exception. For instance, the right to copyright under the law does not include the right to control; (a) Fair dealing for purpose of research, private use, criticism or review or the reporting of current events. This is subject to the condition that if the use is public, it shall be accompanied by an acknowledgment of the title of the work and its authorship. The exemption is where the work is incidentally included in a broadcast. (b) The doing of any of the aforesaid acts of parody or caricature; (c) The inclusion in a film or broadcast of an artistic work situated in a place where it can be viewed by the public. (d) The reproduction and distribution of copies of any artistic work permanently situated in a place where it can be viewed by the public. (e) The incidental inclusion of an artistic in a film or broadcast. (f) The inclusion in a collection of literary or musical work which includes not more than two excerpts from the work, if the collection bears a statement that it is designed for educational use and includes an acknowledgement of the title and authorship of the work; (g) The broadcasting of a work if the broadcast is approved by the broadcasting authority as an educational broadcast, any reproduction for educational use which shall be destroyed after use within 12 months, copying of literary or musical with sufficient acknowledgment which must not be for commercial purposes. (h) Use under the direction or control of the Government, public libraries on the condition that it is not used for revenue generation. (i) Exceptional documentary to be kept for commercial purposes. (j) News of the day publicly broadcast or communicated but no fee must be charged. (k) For use in judicial proceedings (l) Making of more than three copies of a book in a pamphlet, sheet music, map, chart or plan) by or under the direction of the person in charge of a public library which is not available for sale in Nigeria, (m) Reproduction for the purpose of research or private study of an unpublished work. (n) Government sponsored for the promotion of the welfare of other disabled persons for the exclusive use. First Ownership of Copyright The Copyright Act is quite extensive in the range of protection that it guarantees to authors and producers of various works. The copyright conferred under sections 2 and 3 of the Act shall initially vest in the author. Despite the provisions in the Act for co-ownership of copyright, where a work is commissioned by a person who is not the author’s employer under a contract of service or apprenticeship, or not having been so commissioned, is made in the course of the author’s employment, the copyright shall belong in the first instance to the author unless otherwise stipulated in writing under a contract. The author will not be regarded as the first owner of the copyright in a work, even where a literary, artistic or musical work is made by the author in the course of his employment by the proprietor of newspaper, magazine or similar periodical under a contract of service or apprenticeship as is so made for the purpose of publication in newspaper, magazine or similar periodical. In this instance, the proprietor shall in the absence of any agreement to the contract be the first owner of copyright in the work. Right to Claim Authorship Again, it is the law that the author of a work which copyright subsists has the right to claim authorship of his work. The ground of his claim must be predicated on any of the acts generally within the provisions of the Act. But the author cannot succeed in his claim when the work is included incidentally or accidentally when reporting current events by means of broadcasting. The author is also allowed to object and seek relief when there is distortion, mutilation or other modification or any other derogatory action in relation to his work. This right is only exercisable where such would be or is prejudicial to his honour or reputation. The author or his heirs and successors in title has the right in perpetuity. The right is inalienable and imprescriptibly according to the Act. This is in contrast with the provisions of section 2 of the Act and found under the first schedule to the Act. For instance, the schedule stated that the copyright in literary, musical or artistic works other than photographs shall expire seventy years after the end of the year in which the author dies. A learned author, Ozioko (2005) however opined as follows: Copyright does not however tenure in perpetuity. Its duration is limited to either the life time of the author or certain number of years after his death or certain number of years from the date of first publication or production of the work as the case maybe. After its expiration, the work is said to fall into the public domain and can be utilized by any person without liability. Notably, the Act made effort to balance public interests with that of an individual. It struck a balance between the two conflicting interest by not giving the author a perpetual monopoly over his work and also by providing some exemptions from copyright control with the limited period he enjoys the monopoly. A Licencee Generally, under the law as highlighted above, the author is recognized as the only person who can authorize publication of the book. However, the law made certain provisions on assignment and licensing of copyright. The copyright in a work is therefore transmissible by assignment, by testamentary disposition or operation of law as movable property. The assignment may be limited so as to apply to only some of the acts which the owner of the copyright has the exclusive right to control or to a part only of the period of the copyright or to a specified country or other geographical area. The grant of a non-exclusive licencee to do an act, the doing of which is controlled by copyright may be written or oral. It may also be inferred from conduct. The law envisages that where there are two copyright owners, the grant by one owner shall have the same effect; however, that is subject to the contract existing between them. Persons are deemed to be co-owner (a) If they share a joint interest in the whole or part of a copyright or (b) If they have interest in the various copyright in a composite production, that is, a production consisting of two or more works. An author and publisher contract is an agreement under which the author permits the publisher to use those publishing rights under specified conditions. The payment of royalty or some other fees is usually one of the chief conditions. Another important condition is the author’s warranty. The law regards it that an author has an inalienable right to a share in the proceeds of any sale of that work or manuscript by public auction or through a dealer whatever method used by the later to carry out the operation. However, the above condition shall be determined by the Nigerian Copyright Commission. The Regulatory Bodies in the Realm of Copyright a. Nigeria Copyright Commission A landmark innovation of the Nigerian Copyright Act is the establishment of an autonomous regulatory body for the administration of the law. The Nigerian Copyright law under the 1988 Decree nor the Copyright Act of 1970 did not provide for such. The then Nigerian Copyright Council was not imbued with such powers. Prior to the 1988 Decree, the Copyright Act of 1970 did not make provision for an independent administrative body. This was also captured in the observation of Asein thus; …..Individual right owners were left to sort things out themselves. This omission in the law alienated right owners from the statutes and hindered this implementation of those government policies which were intended for the promotion of copyright. Government was also denied the benefit of broad based expert advice on matters relating to copyright. The Act provides that there shall be established a body to be known as the Nigerian Copyright Commission. The Commission is a body corporate with perpetual succession and a common seal and may sue and be sued in its corporate name. The primary functions of the Commission under the Act include a. Responsibility for all matters affecting copyright in Nigeria. b. Monitor and supervise Nigerian’s position in relation to International convention and to advice Government. c. Advising and regulating conditions for sealing of bilateral and multi-lateral agreements between Nigerian and any other country. d. Enlightening and informing the public on matters relating to copyright. e. Maintenance of an effective data bank on authors and their works. b. Copyright Inspectors And Collecting Societies In order to aid and strengthen the administrative, and enforcement structure and actualize the goals of the law, the Act introduced two principal features in the regime, namely: i. The appointment of copyright inspectors with wide policing functions. ii. The establishment and approval of collecting societies for the benefit of copyright owners. The introduction of the two, especially, the appointment of copyright inspectors whose powers include inter alia, to enter, inspect and search buildings, interrogate suspects and arrest persons reasonably suspected of infringing, as well as prosecute such infringers, is a welcome development. It is a vibrant legal framework for the protection of copyright and depicts a hallmark of an effective regulatory system and the regime of enforcement of compliance and practical expression within the administrative and legal framework of the copyright system. Infringement of Copyright Copyright is infringed under section 15 by any person who without the licence or authorization of the owner of the copyright a. Does or causes any other person to do an act, the doing of which is controlled by copyright b. Imports or causes to be imported into Nigeria any copy of a work which, if it had been made in Nigeria would be an infringing copy under this section of the Act. c. Exhibits in public any article in respect of which copyright is infringed under paragraph (1) of this subsection. d. Distribution by way of trade, offers for sale or otherwise or for any purpose prejudicial to the owner of the copyright, any article in respect of which copyright is infringed under paragraph (a) of this subsection. e. Makes or has in his possession plates, master tapes, machines, or equipment used for the purpose of making infringed copies of the work and others. Civil, Criminal regulations and other Remedies. Under the Copyright Act, there are other provisions for civil, criminal and other remedies to deal with almost every conceivable emerging challenge in the area and other allied rights. Indeed, the Act also provided for the adjudication of cases. The Federal High Court exercises jurisdiction over copyright matters. The protection under this area is chronicled by in-built presumptions under the law. It is provided in the Act that in an action for an infringement of copyright in a work, the following shall be presumed unless the contrary is proved; a. That copyright subsists in a work which is the subject matter of an alleged infringement. b. That the plaintiff is the owner of copyright in the work. c. That the name appearing on a work purporting to be the name of the author, is the name of such author. d. That the name appearing on a work purporting to be that of the publishers or product of a work is the name of such publisher or producer. e. Where the author is dead, that the work is an original work f. That is was published or produced at the place and on the date appearing on the work. Criminal Liability It is very unfortunate that our laws do not change with the changing situations. The criminal liability for violators of the Act ranges from a fine of N100 to an amount not exceeding N1000 for every copy dealt with in contravention and a prison term that ranges from a term of six months to a term not exceeding five years. Even the anti-piracy measures which were applauded twenty years ago cannot stand the test of time. The fine not exceeding N50,000 to N500,000 and or a prison term not exceeding twelve months and five years for the specific offences. The criminal liability for violation of performer’s right ranges from N100 to a fine not exceeding N10,000 and or an imprisonment term of twelve months. The Challenges: Despite the laudable protection offered to authors or copyright owners, it has not been easy for authors in Nigeria. There is apparently lack of adequate information on the state of the law on copyright amongst the authors or copyright owners. The presumptions of the law is that for there to be an action for an infringement of copyright in a work, the contrary of the following must be proved; a. That copyright subsists in a work which is the subject matter of an alleged infringement. b. That the plaintiff is the owner of copyright in the work c. That the name appearing on a work purported to be the name of the author is the name of such author. d. That the name appearing on a work purporting to be that of the publisher or producer of a work is the name of such publisher or producer. e. Where the author is dead, that the work is an original work. f. That it was published or produced at the place and on the date appearing on the work. The apparent lethargy and lack of enthusiasm on the part of right owners in the enforcement of their rights is in reality a set back to the progress of authorship. There is need for an integrated long term and continuous enlightenment and education programme for the copyright owners. An effective reward system is very crucial for the development and dissemination of knowledge which is perhaps the principal purposes of the copyright law. It is therefore not an overstatement to say that the success of a copyright system depends on its ability to provide authors the needed incentive by way of remuneration. The royalty as prescribed under the law is yet to be realized by authors. In a contemporary technology - driven society, it is becoming increasingly difficult for authors to earn a living from their creativity due to the influence of modern communication and reproduction facilities which also render the diffusion of works easy and often intractable. Most times the surreptitious infringements done at home or behind closed doors by way of reproduction through electronic devices is a challenge to Nigerian authors. The collection of revenue accruing therefore is a real problem to the system. The impact of digital technology on intellectual property rights has to a large extent been to enable production and distribution of pirated materials despite the legal protection offered by the law. In fact, as book piracy eases, the problem of unauthorized photocopying of copyright works is prevalent. Added to the problem of piracy is the writer/publisher issues. A writer wishing to contribute to the social development of the society sends his or her manuscript to the publisher or if the writer is lucky to have his manuscript published, only a paltry royalty is paid and with no prospect of reprint and book promotion. Another serious challenge of an author is his awareness of the jurisdiction of the Federal High Court to entertain and determine cases on infringement of copyright. Most authors see it as a waste of time and money going to court. Authors are still finding it difficult to explore the opportunity granted by the provisions of the law. Little did the author or even the publisher know that unlike the common law jurisdictions in respect of the infringement, it is permissible for both criminal and civil actions to be taken simultaneously. The law also provides for an order for inspection and seizure of infringing, materials thus; In any action for infringement of any right under this Act where an ex parte application is made to the court, supported by affidavit, that there is any house or premises any infringing copy or any plate, film or contrivance used or intended to be used for making infringing copies or capable of being used for the purpose of making copies or any other article, book or document by means of or in relation to which any infringement under this Act has been committed, the court may issue an order upon such terms as it deems just, authorizing the applicant to enter the house or premises at any reasonable time by day or night accompanied by a police officer not below the rank of an Assistant Superintendent of Police and (a) seize, detain and preserve any such copy or (b) Inspect all or any documents in the custody or under the control of the defendant relating to the action. The provision is a statutory equivalent of the English Anton Piller Order which derives its name from the case of Anton Piller KG v Manufacturing process Ltd. It only requires the applicant to have a strong, prima facie case that serious potential damage is likely to be done to him in that the defendant possess vital documents or materials in his possession which is likely to be destroyed unless the plaintiff is allowed to remove them into his custody pending actual trial. Moreover, authors that are aware of the remedies available in going to court and which the law provided for still contend with remedies available to them as the monetary compensation is inappropriate. Even when the matters come to court, the penalties imposed under the Act against the persons who pirated their works is glaringly inadequate. For instance, the Act gave the prison term of two years or below or an option of an amount not exceeding N100 for every copy or both, as punishment for violation of the Act. Again, in award of damages, the courts awards paltry sum. In Yemitan V. Daily Times (Nig) Ltd, the court awarded the sum of N25,000.00 because of what the court termed the “flagrancy of the infringement and the profit benefit to the defendants arising from the infringement. Copyright Inspectors and the Nigerian Copyright Commission are lacking in the discharge of their responsibilities of monitoring activities of pirates, effective arrests and the prosecution of offenders generally. Again, the creation of collecting society by the Act is not yielding the much desired result as not much progress had been recorded about registered society’s that will act on behalf of copyright owners in Nigeria. In Musical Copyright Society (Nig) Ltd v. Details (Nig) Ltd the plaintiff purported to be acting for various copyright owners and sought to prevent the defendant from dealing with the same works. At the trial, it was revealed that they had earlier unsuccessfully applied to be registered by the Nigerian Copyright Commission. The case was dismissed as the court held the plaintiff lacked the capacity to sue. Conclusion Copyright is unique as well as special genre of proprietary interest giving rise to the need for unique statutory protection. The government of Nigeria has put in place a legal framework for the protection of copyright owners. The Nigerian Copyright Act registered a creative work as a product of the mind and accordingly manifestation of author’s personality as well as his economic asset. The author is therefore entitled to an exclusive right in all forms of economic exploitation of his work, whatever the value but subject to the overriding interest of the society. However, the lofty goal in the Act in favour of the author is yet to be realized and has affected the sustainable growth in creativity in Nigeria. Recommendations i. The Nigerian Copyright Commission should reinvigorate the enforcement arms/agencies like the copyright inspectors and collecting society. Serious enlightenment programmes and education should be continuously organized. Anti-piracy policies should be mapped out and strengthened for the realization of the goals set out under the Act. ii. Registered collecting societies should be encouraged to join the agencies in collectively formulating strategies for the fight against piracy. This will encourage an effective reward system which is crucial for the development and dissemination of knowledge which is perhaps the principal purpose of the Copyright Act. The collecting society machinery should be established and the Commission should assist in establishing a collecting society for any class of copyright owner. iii. Copyright owners should be encouraged to pursue copyright actions instead of staying away or reluctance as a result of fear of delays and encouraged that the cases will be determined expeditiously. iv. Courts should use their powers in awarding commensurate damages as this will rekindle the hope of copyright owners in believing in the efficacy and powers of the judiciary in assuaging their feelings. For instance, in Masterpiece Investments LTD & Anor v Worldwide Business Media LTD & 2 ors where the defendants unlawfully copied and duplicated the work of the plaintiff without their consent, the defendants were found liable and special damages of N200,000.00 and exemplary or punitive damages of N400,000.00 because of vulgarization of the work, unjust enrichment by the defendants was awarded. v. There should be a synergy between the Nigerian Copyright Commission, its agencies namely the police, customs and the court in ensuring that the realization of the goals of the Copyright Act. By this arrangement, the Commission should explore international corroboration in the fight against copyright violations. None signatories to the conventions should be tackled to bring all of them under the regime. vi. There is need for further amendment of the Act to accommodate the position of admissibility on the emerging issue of computer printout relating it to the Evidence Act provisions. For instance, in RV Pettigrew where it was held that a computer printout is not admissible because the information it contained was not supplied by a person who had or could reasonably be said to have personal knowledge of that information. vii. Nigeria should also emulate United States that has through the Digital Millennium Copyright Act put in place the necessary legal machinery designed to implement WIPO Copyright Treaty (WCT) and WIPO performances and phonograms Treaty (WPPT), as well as enforcement of online infringement of copyright, liabilities, limitations and others. Exploiting the provisions of section 33 of the Copyright Act is very necessary. viii. The present penalties prescribed for criminal infringement of copyright is very low. The amendment of sections 20, 21, 23, 30 and 33 to which an upward review is recommended. The penalty to be imposed should be such that will deter the violators and the amount to be imposed should reflect the economic realities of the time. References Ademuga v Ilasammi Press sons (Nig) Ltd (1991) 5 NWLR (pt. 189)82 Copyright Act cap C28, Laws of the Federation of Nigeria, 2004. Evidence Act, Federal Republic of Nigeria, 2011 FHC/L/20/91 unreported case in TA. Odunowo op. cit at 64 Ferodo Ltd V Unibros stores (1980) FSR 489 Garner, B.A. (Ed). (2014) Black’s Law Dictionary, 10th ed (St Paul Minn: Thompson Reuters) Hon. Justice TA Odunowo Nigerian Copyright Law: A juridical overview in A decade of copyright law in KGBOguakwa, Implementing the Copyright Decree, (2005) This Day Newspapers, 1 (109) p. 15 Smith, D.C. (1989) A Guide to Book Publishing. Washington: University Press.p7. Ozioko, M.V.C. (2005) International Law and the protection of intellectual property Rights – Present realities and future challenges, Unizik Law Journal 4 (1), p. 137. Universal Declaration of Human Rights, Article 27(2)